PENGARUH PEMAHAMAN AGAMA ORANG TUA TERHADAP KEDISIPLINAN SISWA DALAM MELAKSANAKAN SHALAT DI SMK NEGERI 2 KOTA BENGKULU - Ria Amara; Edi Ansyah; Adam Nasution (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2026)
This study aims to determine the effect of parents’ religious understanding on students’ discipline in performing prayers at SMK Negeri 2 in Bengkulu City, to describe the extent of this effect, and to identify the factors that influence it. This study employed a quantitative method and was analyzed using simple linear regression. The population consisted of all 324 eleventh-grade students, while the sample was selected using purposive sampling. Data were collected via a questionnaire. To test the effect of the independent variable on the dependent variable, hypothesis testing was conducted using simple linear regression with the t-test (partial). Based on the calculations performed, the calculated t-value was positive and statistically significant at 0.002. This value is less than α (alpha) = 0.05 (0.002 < 0.05), so H₀ is rejected and H₁ is accepted. The results of this study show that there is a significant relationship between parents’ religious understanding and students’ discipline in performing prayers, thereby confirming the research hypothesis. This study provides empirical evidence indicating the extent to which parents’ religious understanding contributes to students’ discipline in performing prayers. Based on the calculations performed, approximately 86.2% of students’ discipline in performing prayers is influenced by their parents’ religious understanding, while the remaining 13.8% is influenced by other factors outside the variables examined in this study, namely social environment or peers, as well as social media. It can be concluded that the greater the contribution of parents’ religious understanding, the higher the level of students’ discipline in performing prayers.